2019
DOI: 10.1080/17435390.2019.1651920
|View full text |Cite
|
Sign up to set email alerts
|

Integration of inflammation, fibrosis, and cancer induced by carbon nanotubes

Abstract: Carbon nanotubes (CNTs) are nanomaterials with unique physicochemical properties that are targets of great interest for industrial and commercial applications. Notwithstanding, some characteristics of CNTs are associated with adverse outcomes from exposure to pathogenic particulates, raising concerns over health risks in exposed workers and consumers. Indeed, certain forms of CNTs induce a range of harmful effects in laboratory animals, among which inflammation, fibrosis, and cancer are consistently observed f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(63 citation statements)
references
References 171 publications
2
58
0
3
Order By: Relevance
“…The chronic immune outcome is dominated by type 2 response, in which alternatively activated M2 macrophages are enriched and activated (Dong and Ma, 2018b). In summary, the pulmonary responses to CNT exposure initiate from acute inflammatory and fibrotic events, and progress to chronic inflammation and fibrosis (Dong and Ma, 2019b). The biphasic process of CNTinduced lesions resembles that elicited by the deposition of fibrogenic foreign bodies, such as insoluble dusts and large biologic masses, in the lung.…”
Section: Cnt-induced Lung Inflammation and Fibrosismentioning
confidence: 99%
See 2 more Smart Citations
“…The chronic immune outcome is dominated by type 2 response, in which alternatively activated M2 macrophages are enriched and activated (Dong and Ma, 2018b). In summary, the pulmonary responses to CNT exposure initiate from acute inflammatory and fibrotic events, and progress to chronic inflammation and fibrosis (Dong and Ma, 2019b). The biphasic process of CNTinduced lesions resembles that elicited by the deposition of fibrogenic foreign bodies, such as insoluble dusts and large biologic masses, in the lung.…”
Section: Cnt-induced Lung Inflammation and Fibrosismentioning
confidence: 99%
“…Remarkable acute immune response is induced in CNTexposed lungs, which precedes and accompanies acute fibrotic response. This phenomenon is reminiscent of inflammationdriven fibrosis occurring in many human diseases, such as IPF, COPD, and systemic sclerosis (Dong and Ma, 2019b). CNTexposed lungs therefore provide a model system to study the role of inflammation in the initiation and progression of fibrosis development, which cannot be performed in other fibrosis models due to the lack of marked acute immune response therein.…”
Section: Cnt-induced Lung Inflammation and Fibrosismentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of the safety profile of the CNTs, studies suggested that endocytosis of the CNTs induces oxidative stress to the cells, revealing a close connection between CNTs and inflammation, fibrosis, and cancer, impeding the translational value of this nanocarrier [41,42]. In addition, the toxicity of CNTs is not only related to their shape but also to their surface charge [40,[43][44][45][46].…”
Section: Carbon Nanotubesmentioning
confidence: 99%
“…In animal research, CNT-long exposure could induce persistent inflammation, lung cancer, fibrosis, and gene destruction in the lung. 23,24 In general, the mechanisms of creating toxicity are divided into five sections as apoptosis, reactive oxygen species, free radical formation, the formation of granuloma, and increased inflammatory response. Due to the above mechanisms, types of toxicities in cells, skin, gene, liver, cardiovascular, pulmonary, and carcinogens substance, are created.…”
Section: The Pulmonary Toxicity Assessment Of Carbon Nanotubesmentioning
confidence: 99%